Murus et pomerium : réflexions sur la fonction des remparts protohistoriques - Stephan Fichtl (Revue Archéologique du Centre de la France)
This article considers the function of the ramparts of late La Tène oppida. If the three traditional functions exist for these sites (defensive, show and symbolic) it is however the symbolic function which is of overriding importance. A parallel can thus be drawn with the idea of the pomerium, well-known in the Etrusco-Roman world. In effect the symbolic delimitations are attested at different levels among the Celts as much for the temenos of sanctuaries as for the territory of the civitas. It is not surprising that the appearance of the first urban sites, the oppida, should be accompanied by a symbolic delimitation as with Greek and Roman towns.